Mekanisme Pengembangan Bisnis Sarang Burung Walet di Kabupaten Pidie Jaya - Hartanti Dewi (Asia-Pacific Journal of Public Policy, 2021)
Pidie Jaya Regency from 2012 to 2015 has never resulted in achieving the realization of the swallow's nest business target. This study aims to identify and describe the mechanism for setting targets and government action plans to increase acceptance of the realization of the swiftlet nest business in Pidie Jaya Regency, Aceh, Indonesia. This research was conducted with a descriptive qualitative approach. The data were obtained through observation, interviews, and documentation, while the informants of this study were determined based on the propositional technique. The results of this study indicate that the mechanism for determining the object of the swallow's nest business has been determined by the DPPKAD (The Regional Revenue, Financial, and Asset Management Agencies) service at 8% of the harvest. The determination of the swallow's nest business target in Pidie Jaya Regency is based on an estimate/prediction, it is still not accomplished mathematically and visits the real thing in the field. To increase the acceptance of the swallow's nest business realization, the DPPKAD Office will carry out socialization, appeals, installation of billboards, and broadcasting of advertisements on radio, and will cooperate with the village leader parties to stay business subjects. A recommendation for this research is that the DPKKAD should carry out its duties by establishing procedures or qanuns (local regulations).